Financial contagion: evolutionary optimisation of a multinational agent-based model - Guglielmo Maria Caporale; Antoaneta Serguieva; Hao Wu (Center for Economic Studies and ifo Institute (CESifo), 2008)
Over the past two decades, financial market crises with similar features have occurred in different regions of the world. Unstable cross-market linkages during a crisis are referred to as financial contagion. We simulate crisis transmission in the context of a model of market participants adopting various strategies; this allows testing for financial contagion under alternative scenarios. Using a minority game approach, we develop an agent-based multinational model and investigate the reasons for contagion. Although the phenomenon has been extensively investigated in the financial literature, it has not been studied through computational intelligence techniques. Our simulations shed light on parameter values and characteristics which can be exploited to detect contagion at an earlier stage, hence recognising financial crises with the potential to destabilise cross-market linkages. In the real world, such information would be extremely valuable in developing appropriate risk management strategies. - Financial contagion ; minority/majority game ; agent-based model ; evolutionary parameter optimisation
Keywords: C63; C73; F37; 330; Finanzmarktkrise; Ansteckungseffekt; Spieltheorie; Agent-based Model; Welt